Study on the Reproductive Group Behavior of Schizothorax wangchiachii Based on Acoustic Telemetry - Bo Li; Fanxu Hu; Wenjing Li; Wei Su; Jiazhi Zhu; Wei Jiang (Fishes, 2025)
To investigate the group behavioral characteristics of Schizothorax wangchiachii during the spawning period, we used acoustic telemetry to track 10 mature individuals (4 females, 12 males) in a semi-controlled stream section (28.1 m × 5.8 m) simulating natural spawning microhabitats from 23 to 26 January 2024. By integrating trajectory similarity analysis and wavelet transform, we examined the aggregation patterns and activity rhythms during natural spawning events. The population formed two relatively stable subgroups, with significantly shorter inter-individual distances during the day (1.69 ± 0.72 m) than at night (2.54 ± 0.85 m, p < 0.01). Aggregation behavior exhibited a dominant ultradian rhythm of 16.5 h, with stable clustering between 09:00 and 16:00 (spawning window: 13:40–14:20) and dispersal from 19:00 to 00:00. Group activity followed a decreasing-then-increasing trend, with higher nighttime activity. Males were more active than females (F = 51.89, p < 0.01); female activity peaked on the spawning day and was influenced by reproductive progression, while male activity was mainly driven by diel rhythms (p < 0.01). A weak positive correlation was found between active time and inter-individual distance in both sexes (r = 0.32, p < 0.05), indicating reduced activity when aggregated. These findings provide insight into the temporal coordination and spatial regulation of reproductive behavior under semi-controlled conditions. However, due to the short monitoring period and experimental setup, caution is warranted when generalizing to the full reproductive season or fully natural habitats.